The Virgin Goddess, Studies in the Pagan and Christian Roots of Mariology. - Stephen Benko (Numen Book Series, 2004)
The contemporary search for the feminine face of God is requiring a re-examination of the relationship of Christianity to the pagan world in which it came to birth. Stephen Benko approaches this study as both an historian and a Christian believer. Inquiring into extra-biblical sources of Marian piety, belief and doctrine, he proposes 'that there is a direct line, unbroken and clearly discernible, from the goddess-cults of the ancients to the reverence paid and eventually the cult accorded to the Virgin Mary.' Chapter by chapter he seeks to establish his conclusion that 'in Mariology the Christian genius preserved and transformed some of the best and noblest ideas that paganism developed. Rather than being a 'regression' into Paganism, Mariology is a progression toward a clearer and better understanding of the feminine aspect of the divine and the role of the female in the history of salvation.' This publication has also been published in hardback, please click here for details.